Vaksin DNA: Vaksin Generasi Keempat - Radji, Maksum (UI Scholars Hub, 2009)
Vaccines have been developed for a range of different infectious diseases. The complex-ity of microbial infections requires novel approaches to vaccine design. The first-generation of vaccines were live attenuated pathogens. Because of safety concerns, the second-generation of vaccines, chemically or physically inactivated pathogens were later developed. Purified or synthetic proteins represent a third generation, and recent advances in molecular biology and genetic engineering have led to the development of the fourth vaccine generation, which includes DNA and virus vector-based vaccines. This review discusses on the genetic elements and construction of DNA vaccines, comparison of DNA vaccines and conventional vaccines, the benefits and limitations of DNA vaccines, and the advances of genetic vaccine development over the last decade.